Особливості стратегії максимізації вартості підприємства коньячної галузі України - Могилова, А.Ю. (Культура народов Причерноморья, 2013)
Обґрунтовано важливість вирішення проблеми зростання вартості підприємства в
контексті підвищення його капіталізації. Враховуючи те, що прогнозувати зростання вартості
підприємства з високою ймовірністю можна за умов чіткого формулювання стратегії та виокремлення
її основних складових (часткових стратегій), було визначено часткові стратегії максимізації вартості
підприємства коньячної галузі. Сформовано комплекс ключових факторів успіху для промислового
підприємства та деталізовано характерні ознаки кожного фактору з урахуванням галузевих
особливостей коньячного виробництва в Україні. Обоснована важность решения проблемы роста стоимости предприятия в контексте
повышения его капитализации. Учитывая то, что прогнозировать рост стоимости предприятия с
высокой вероятностью можно при условии четкого формулирования стратегии и выделения ее
основных составляющих (частных стратегий), были определены частные стратегии максимизации
стоимости предприятий коньячной отрасли. Сформирован комплекс ключевых факторов успеха для
промышленного предприятия и детализированы характерные черты каждого фактора с учетом
отраслевых особенностей коньячного производства в Украине. On the growth of capitalization of the enterprise can be inferred if the growth of its value. Therefore
the important question is cost management and the formation of strategic enterprises to improve it. And to
maximize the value of the company is a strategic goal. Given that the forecast growth in enterprise value with
high probability we can, with a clear strategy formulation and allocation of its main components (partial
strategies) were defined partial strategies to maximize the value of enterprises cognac industry, namely: 1. The
exit strategy for IPO; 2. Clustering Strategy; 3. The strategy of vertical integration; 4. Production strategy; 5.
The funding strategy; 6. HR Strategy. Formed a set of key success factors for an industrial company: 1. Brand
Enterprise; 2. The market share of the enterprise; 3. The optimum level of performance; 4. Equipment and its
quality; 5. Product portfolio and product quality; 6. Pricing policy; 7. Financial performance. The
characteristic features of each of the factors are detailed with the industry characteristics of cognac production
in Ukraine. The results of an effective strategy to maximize the value of the company of the cognac industry will
be: strengthening the competitive position; high profitability, regional expansion, customer loyalty, staff loyalty,
ensuring future growth, company-brand.